Currency Crises and Foreign Reserves : A Simple Model - Disyatat, Piti (IMF Working Papers; Working Paper ;, 2001)
This paper addresses the important question of how far a government will run down its stock of foreign reserves in a defense of a fixed exchange rate. An optimizing model of currency crisis is presented in which the decision of whether or not to borrow in a defense of a peg is explicitly analyzed. The threshold level of reserves is then determined endogenously and shown to be a function of fundamental economic variables. The analysis also demonstrates how an increase in the level of reserves, a credit-rating upgrade, or the imposition of capital controls can remove the multiplicity of equilibria.